Randomized phase 2 trial on refinement of early-stage NSCLC adjuvant chemotherapy with cisplatin and pemetrexed versus cisplatin and vinorelbine: the TREAT study - Kreuter, Michael (Annals of oncology, 2013)
BACKGROUND: Adjuvant chemotherapy is beneficial in non-small-cell lung cancer (NSCLC). However, balancing toxicity and efficacy mandates improvement. PATIENTS AND METHODS: Patients with completely resected stages IB-pT3N1 NSCLC were randomly assigned to either four cycles cisplatin (C: 50 mg/m(2) day (d)1 + 8) and vinorelbine (V: 25 mg/m(2) d1, 8, 15, 22) q4 weeks or four cycles cisplatin (75 mg/m(2) d1) and pemetrexed (Px: 500 mg/m(2) d1) q3 weeks. Primary objective was the clinical feasibility rate (no grade (G)4 neutropenia/thrombocytopenia or thrombocytopenia with bleeding, no G3/4 febrile neutropenia or non-hematological toxicity; no premature withdrawal/death). Secondary objectives were drug delivery and efficacy. RESULTS: One hundred and thirty two patients were randomized (stages: 38% IB, 10% IIA, 47% IIB, 5% pT3pN1; histology: 43% squamous, 57% non-squamous). The feasibility rates were 95.5% (cisplatin and pemetrexed, CPx) and 75.4% (cisplatin and vinorelbine, CVb) (P = 0.001); hematological G3/4 toxic effects were 10% (CPx) and 74% (CVb) (P < 0.001), non-hematological toxic effects were comparable (33% and 31%, P = 0.798). Delivery of total mean doses was 90% of planned with CPx, but 66% (cisplatin) and 64% (vinorelbine) with CVb (P < 0.0001). The median number of cycles [treatment time (weeks)] was 4 for CPx (11.2) and 3 for CVb (9.9). Time to withdrawal from therapy differed significantly between arms favoring CPx (P < 0.001). CONCLUSION: Adjuvant chemotherapy with CPx is safe and feasible with less toxicity and superior dose delivery compared with CVb.
Published online: 15 November 2012
Gesehen am 26.04.2018